Infections in Pediatric Patients With Burn Injury: 6 Years of Experience. Issue 1 (12th October 2022) - Karaaslan, Ayşe; Çetin, Ceren; Köle, Mehmet Tolga; Dereli, Murat; Demir Tekol, Serap; Filinte, Gaye; Akin, Yasemin
Abstract : Background: This study aimed to determine the frequency of bloodstream and wound infections and their possible risk factors in hospitalized children with burn injury. Methods: We performed this retrospective descriptive study from 2015 to 2021. The study subjects consisted of all the pediatric patients hospitalized in the burn unit, from whom microorganisms were isolated either from blood or wound culture samples. Results: We detected a total of 142 microorganisms from 97 blood culture samples and 45 wound culture samples. Among the 115 patients, 44 (38.3%) were females and 71 (61.7%) were males, with a median age of 21 months (interquartile range: 14–39 months). Gram-positive bacteria were the most common causative agents of bloodstream infections in patients with burns (54.6%), followed by Gram-negative bacteria (32.9%) and fungi (12.3%). Gram-negative bacteria were the most common causative agent of wound infections (86.7%). Prolonged hospitalization positively correlated with the extent of the burn surface area ( P : 0.031), degree of burn ( P : 0.001), use of central venous catheter ( P : 0.028), and intensive care unit stay ( P : 0.044). Independent risk factors for Gram-negative bacteremia and Gram-negative wound infections were the extent of the burn surface area ( P : 0.018), degree of burn ( P : 0.024) and intensive care unit stay ( P : 0.023). The independent risk factor for fungemia was prolonged hospitalization ( P : 0.026). Conclusions: To reduce infections, minimizing invasive procedures using a multidisciplinary approach would be beneficial, especially in patients who have a large burn surface area and are expected to have a long hospital stay.